Evidence for expression and function of phosphodiesterase type 5 (PDE-V) in rat resistance arteries. - Sampson, L; Hinton, J; Garland, C (2001)
Evidence is provided for expression and a functional role for phosphodiesterase type V (PDE-V) in the rat isolated small mesenteric artery. The reverse transcription polymerase chain reaction (RT--PCR) demonstrated mRNA for PDE-V, while Western blotting and immunocytochemical studies showed corresponding protein expression. Smooth muscle relaxation to the nitric oxide donor, diethylamine NONOate (DEA NONOate; 1 nM - 10 microM; pEC(50)=6.7+/-0.3) was potentiated significantly by the specific inhibitor of PDE-V, 4-[[3,4-(methylenedioxy)benzyl]amino]-6-chloroquinazoline (MBCQ; 1 microM; pEC(50)=10.5+/-0.04). These data show that PDE-V is expressed in both the smooth muscle and endothelial cells of a resistance artery, and the enzyme can significantly influence nitric oxide-evoked vasorelaxation.